Nutrition Monitoring in Post-Surgery Patient with Type 2 Diabetes Mellitus - Jon Hafan Sutawardana; Trisya Aulia Damayanti; Akhmad Zainur Ridla (Universitas Muhammadiyah Semarang, 2023)
Nutrition for patients with type 2 diabetes mellitus (T2DM) may develop postoperative hyperglycemia. Nutrition monitoring is one way to overcome that condition. This study aims to determine the overview of nutritional monitoring in post-surgery patients with type 2 diabetes mellitus. This study used a literature review design with four databases, PubMed, ScienceDirect, Wiley Online Library, and Google Scholar. The inclusion criteria in this study were the articles published from 2018 to 2022, cohort studies, randomized control trial studies, quasi-experimental studies, case-control studies, and accessible full-text, articles in English and Indonesian, indexed by SINTA or SCIMAGOJR. This study got ten articles discussing nutritional monitoring in post-surgery patients with T2DM. The average glucose level in post-surgery patients with T2DM has increased. These conditions are related to parenteral nutrition and ERAS intervention. Meanwhile, nutritional risk or malnutrition before surgery is related to nutritional status after surgery. Nutrition monitoring is used for glucose control and early identification of nutritional conditions in post-surgery patients with T2DM.